Mucoepidermoid Carcinomas of the Larynx. (December 2022) - Richards, Holden W.; Bertelsen, Caitlin; Hamilton, Bronwyn; Sauer, David; Schindler, Joshua
Objectives: Discussions regarding the specific management and outcomes for laryngeal MEC are limited to very small, single-institution case series. To look further into the diagnosis and management of these uncommon non-squamous cell carcinomas of the larynx, we present 3 recent cases of laryngeal MEC treated at our institution. Methods: Patients at a tertiary hospital treated for MEC between October 2019 and December 2020 were retrospectively identified. Chart review, imaging analysis, and histologic slide creation were completed for all patients. Results: We identified and treated 2 patients with high-grade supraglottic and 1 patient with intermediate-grade glottic MEC. These patients presented to our clinic with a primary complaint of either gradual, worsening dysphonia, dysphagia, or both. All patients underwent laryngovideostroboscopy as well as panendoscopy with directed submucosal biopsy, which was consistent with MEC. MRI was performed in 2 of the cases further elucidating the extent of submucosal spread. PET-CT was performed in all 3 cases, and none demonstrated evidence of regional or distal metastases. Surgically, high-grade MEC lesions were treated with a total laryngectomy. The intermediate MEC lesion was managed with a supracricoid partial laryngectomy (SCPL). Surgical margins were free of tumor in all cases with no nodal metastases by modified radical neck dissection. Radiation therapy was offered to both high-grade MEC patients and declined by one. Radiation was not recommended to the patient with intermediate-grade MEC as we believed that the risk of additional treatment outweighed the benefit. Conclusion: We believe that MEC of the larynx should be considered in patients with atypical submucosal laryngeal masses. Laryngovideostroboscopy, MRI, and PET imaging may be valuable in determining the extent of the lesions and planning appropriate surgery. Postoperative radiation therapy should be considered a per tumor grade in other more studied sites, as there is no data on efficacy in laryngeal MEC.